Divergent patterns of matrix metalloproteinase activity during wound healing in ileum and colon of rats - Seifert, W F; Wobbes, T; Hendriks, T (Gut, 1996)
BACKGROUND: Uncontrolled and increased extracellular matrix degradation during early anastomotic repair in the intestine may reduce wound strength increasing the risk of anastomotic dehiscence. AIMS: To characterise the metalloproteinases present in intact and anastomosed ileum and colon to study their role in matrix degradation after surgery. SUBJECTS: Tissue extracts of uninjured, and of anastomosed rat ileum and colon at postoperative days 1, 2, 3, 7, and 90, were used. METHODS: Metalloproteinases were identified by gelatin and casein zymography. Aminophenylmercuric acetate (APMA) treatment was used to activate latent metalloproteinases. RESULTS: Both uninjured ileum and colon contained a 60 and 67 kDa activity, but a 54 and 72 kDa gelatinase was present in ileum only, and a 51 kDa activity in colon only. APMA treatment converted the 60 kDa protease to 54 and 51 kDa forms and the 72 kDa protease to the 67 kDa form. These gelatinases may correspond to latent and active forms of MMP 1 and MMP 2, respectively. Additional metalloproteinases were observed after anastomotic construction. Both ileum and colon contained 95 and 230 kDa gelatinases, which were converted to 83 and 76 kDa forms by APMA. They may be the latent and active forms of MMP 9, respectively. Gelatinolytic activities of 25 and 28 kDa were only found in anastomosed ileum. Caseinolytic activities were only found in ileum extracts and those were most prominent at day 1, 2, and 3 after surgery. CONCLUSIONS: The metalloproteinase pattern in ileum and colon differ considerably suggesting that matrix degradation after anastomotic construction may also vary.